2002
DOI: 10.1161/01.cir.0000030187.39852.a7
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Unexcitable Scar Mapping Based on Pacing Threshold for Identification of the Reentry Circuit Isthmus

Abstract: Background-We hypothesized that delineating electrically unexcitable scar (EUS) within low-voltage infarct regions will locate reentry circuit isthmuses by defining their borders. The pacing threshold and electrogram amplitude that best determines EUS is unknown. Methods and Results-The change in dimension of the virtual electrode was estimated in 11 patients and observed to increase by 4.4Ϯ2.5 mm as stimulus strength increases from threshold (2.9Ϯ1.8 mA) to 10 mA. EUS was defined as a threshold Ͼ10 mA. In 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
237
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(247 citation statements)
references
References 23 publications
8
237
0
2
Order By: Relevance
“…CCs are relatively small compared with the scar areas; therefore, this method could permit focus on the diagnostic techniques and ablation to defined areas; in those patients without CCs on the voltage map, a more timedemanding approach could be used. 10 This procedure would allow the ablation of some nontolerated or noninducible VT not approachable by conventional entrainment mapping. Regarding the ablation guided by E-ICD searching, what additional advantage is afforded by channel identification?…”
Section: Advantages Of Ablation Of the Isthmusmentioning
confidence: 99%
See 1 more Smart Citation
“…CCs are relatively small compared with the scar areas; therefore, this method could permit focus on the diagnostic techniques and ablation to defined areas; in those patients without CCs on the voltage map, a more timedemanding approach could be used. 10 This procedure would allow the ablation of some nontolerated or noninducible VT not approachable by conventional entrainment mapping. Regarding the ablation guided by E-ICD searching, what additional advantage is afforded by channel identification?…”
Section: Advantages Of Ablation Of the Isthmusmentioning
confidence: 99%
“…9 The identification of these CCs before induction of VT may facilitate mapping and/or ablation of tolerated and unmappable VT. Scar mapping based on pacing threshold has been used for the identification of nonconducting tissue that borders viable myocardium during sinus rhythm (SR). 10 To simplify the identification of these CCs during SR, we hypothesized that conducting bundles should have larger voltage amplitude than nonconducting scar. Therefore, voltage maps of the left ventricle might show channels inside the scar, provided that an adequate adjustment of voltage definition of nonconducting scar is used.…”
mentioning
confidence: 99%
“…7 Offline analysis of the digitally stored electrograms and pace maps was performed on the Bard EP system with the use of on-screen calipers at a sweep speed of 200 mm/s. Pace maps were physically searched and matched for at least 11 of 12-lead matches in the surface ECG QRS morphology.…”
Section: Vt Channel Localizationmentioning
confidence: 99%
“…5 As an alternative, substrate-based ablation strategies emphasize targeting all excitable abnormal electrograms within the scar. 6,7 The splitting in fractionated, late, and very late potentials is considered indicative of underlying surviving myocyte bundles with discontinuous conduction. [8][9][10] However, the information content of a VT supporting channel remains obscure in this scheme of abnormal electrogram classification, and, in fact, many are innocuous bystanders.…”
mentioning
confidence: 99%
“…The target VT is rendered acutely non-inducible in 70-90 % of patients. 7,49 The success rate of abolishing all inducible VTs is significantly lower (approximately 50 %). 8,50 A recent meta-analysis of four randomised and one observational study of VT ablation for structural heart disease demonstrated a significant 38 % reduction in VT recurrence compared with medical therapy.…”
Section: Scar-related Ventricular Tachycardiamentioning
confidence: 99%